Filtro ativo de potência paralelo trifásico utilizando a técnica de controle por ciclo. - Lucena, Daiana Correia de (2015)
The high use of reactive and non linear loads connected to the power grid have been led to a growing concern about power quality and this have been promote development of controlled rectifiers and parallel active filters using different control techniques. At this work is done a review of One Cycle Control (OCC) technique, applied to a Parallel Active Power Filter, instead other control techniques, implemented over DSP. The control strategy guarantee the unity power factor and the reduction of harmonics currents, in this system no grid voltage sensors are used. The validation of this work occurred through simulations in the software PSCAD and experimental results to settings of a parallel active power filter with a nonlinear and unbalanced load and for a a nonlinear and balanced load with a power grid which have common mode voltage.